Living on the edge: Forest cover threshold effect on endangered maned sloth occurrence in Atlantic Forest - Santos, Paloma Marques [UNESP] (2019)
Habitat loss and the isolation of remaining habitats are undoubtedly the two greatest threats to biodiversity conservation, especially for the maned sloth, due to its ecological restrictions. In this study, we identified a critical threshold of forest cover for maned sloth occurrence and explored the effects of other local and landscape variables. We sampled 68 sites, where we searched for the maned sloth and collected local habitat variables. We calculated the percentage of forest cover and open areas, assessing the appropriated scale through model selection. We used occupancy models and model selection methods to identify the threshold and assess occupancy and detection probabilities. The occupancy probability of the maned sloth is 0.97, but it decreases abruptly at 35% of forest cover, reaching zero in areas with less than 20% of forest cover. The two landscape variables are the most important predictors of sloth occupancy, based on the cumulative weight of evidence, were: Forest cover (78%) and Open areas cover (46%); the latter influencing negatively maned sloth occupancy. This is the first attempt to identify the habitat requirements of the threatened maned sloth in a fragmented area using landscape and local variables. Our results imply that conservation of maned sloth will benefit from an increase in the amount of native forest at the landscape scale. Given difficulties in the creation of new public protected areas, this improvement could be achieved via the recovery of areas located in private properties that are protected by the Brazilian Forest Code.